Memory practices in the defense of life and territory in Buenaventura, Colombia (1960-2018) (2020)
In Colombia, the practices of memory are the product of the action of multiple agents, mainly social movements, organizational platforms, and work collectives. In the case of Buenaventura (Colombia), these social agents have used a great variety of cultural and political repertoires in order to defend life and imagine possible futures in territories affected by structural violence and historical damage. This article identifies, resorting to a historical perspective, how many of the repertoires of resistance to violence in Buenaventura take place during the period between 1960 and 2018. This article is the result of a research exercise that was carried out in the city between 2016 and 2019, which implied the development of fieldwork, interviews with key actors in the territory, a review, and analysis of national and local press, as well as the systematization of information coming from secondary sources as well as personal and administrative documents. The main conclusion of this article is that the practices of memory in Buenaventura, more than having a cathartic function regarding individual or collective pain, contribute to the historical configuration of spatialities of resistance and the strengthening of the organizational fabrics in the defense of life and the territory.